2011
DOI: 10.4161/psb.6.12.18239
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and divergence of the photoregulation of pigmentation and cellular morphology inFremyella diplosiphon

Abstract: Photosynthetic pigment accumulation and cellular and filament morphology are regulated reversibly by green light (GL) and red light (RL) in the cyanobacterium Fremyella diplosiphon during complementary chromatic adaptation (CCA). The photoreceptor RcaE (regulator of chromatic adaptation), which appears to function as a light-responsive sensor kinase, controls both of these responses. Recent findings indicate that downstream of RcaE, the signaling pathways leading to light-dependent changes in morphology or pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Even though the bacterial life cycle is usually the major determinant of morphological traits, including cell size, several studies reported that cyanobacteria modify their morphology to optimize their functionality to exogenous factors in natural contexts ( Montgomery, 2015 ). However, the mechanisms by which light conditions, including light intensity, influence cell morphology, including cell size, are understudied ( Pattanaik, Whitaker & Montgomery, 2011 ). Table 1 shows Synechocystis cell size changes in response to increasing light intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the bacterial life cycle is usually the major determinant of morphological traits, including cell size, several studies reported that cyanobacteria modify their morphology to optimize their functionality to exogenous factors in natural contexts ( Montgomery, 2015 ). However, the mechanisms by which light conditions, including light intensity, influence cell morphology, including cell size, are understudied ( Pattanaik, Whitaker & Montgomery, 2011 ). Table 1 shows Synechocystis cell size changes in response to increasing light intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the bacterial life cycle is usually the major determinant of morphological traits, including cell size, several studies reported that cyanobacteria modify their morphology to optimize their functionality to exogenous factors in natural contexts (Montgomery, 2015). However, the mechanisms by which light conditions, including light intensity, influence cell morphology, including cell size, are understudied (Pattanaik, Whitaker & Montgomery, 2011). We then examined the effect of long-term acclimation to increasing intensities of orange-red light by estimating the Chl a content in Synechocystis through the measurement of the OD 680 /OD 720 ratio (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The action spectra of LPOR reveals that it is ineffective in green light, in such cases LIPOR compensates for the low LPOR activity. The members of the (Microchaetaceae) Fremyella diplosiphon (Shui et al, 2009;Pattanaik et al, 2011), (Nostocaceae) N. punctiforme (Hirose et al, 2013), (Rivularariaceae) Gloeotrichia 583 (Stowe et al, 2011) depict an interesting phenotype as an example of the complementary chromatic adaptation by alternating their photosynthetic pigments and enzymes under fluctuating light conditions (Hirose et al, 2013). It would not be hyperbolic to say that they can sense a rainbow of colors ranging from red, blue, green and violet (Grossman, 2003;Bordowitz and Montgomery, 2008;Kehoe, 2010).…”
Section: Impact Of Other Environmental Factors On Lpor Origin and Evo...mentioning
confidence: 99%